Knowledge and perception of doctors regarding antibiotic stewardship in a tertiary care hospital of Southern Punjab. - Moazzam Ali Atif (International Journal of Endorsing Health Science Research, 2022)
Background: Pakistan has been working on Antimicrobial Resistance (AMR) for a decade; unfortunately, there is a lack of concept of antibiotic stewardship in most health setups, especially in the public sector. This study aims to analyze the knowledge and perception of junior physicians towards antibiotic stewardship programs. The need for this knowledge and impact of antimicrobial resistance on antibiotic stewardship ascertain barriers to stewardship acceptance.